Etiology, Clinical Manifestation and Natural Treatments of Psoriasis from the Perspective of Persian Medicine - Mohammadreza Rahbar; Azadeh Zarei; Maryam Ranjbar; Malihe Tabarrai; Laila Shirbeigi (Tehran University of Medical Sciences, 2020)
Psoriasis is an inflammatory and autoimmune disease with unknown etiology. This is a chronic, recurrent, distressing and costly disease, which has a great impact on the quality of life of individuals. Its treatment varies from topical to systemic medication and sometimes with a great deal of side effects. Probably, changing nutritional habits, life style modification and applying preventive measures may reduce the high amount use of chemical drugs and the costs of the disease. This study investigates etiology, clinical manifestation and natural treatments of psoriasis from the perspective of Persian Medicine by which prevention and nutritional recommendations and some treatments can be introduced. Searching selected sources of Persian Medicine including the Canon of Medicine, Zakhirah -E- Kharazm Shahi, Kamel alsanaat, Sharh al-asbab va al-alamat, Tebbe-Akbari, Moalejate Aghili, Exir-e-Azam, three diseases named "Ghooba", "Barase Asvad" and "Saafe-Yabes" were found to be similar to psoriasis in their manifestations. Therefore, study of their specific treatments in the levels of lifestyle management more importantly nutrition and herbal therapy could be noteworthy for the future studies.